2022
DOI: 10.3389/fimmu.2022.888713
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Polarization Of Tumor-Associated Macrophages In Cancer Immunotherapy

Abstract: Different stimuli can polarize macrophages into two basic types, M1 and M2. Tumor-associated macrophages (TAMs) in the tumor microenvironment (TME) are composed of heterogeneous subpopulations, which include the M1 anti-tumor and M2 pro-tumor phenotypes. TAMs predominantly play a M2-like tumor-promoting role in the TME and regulate various malignant effects, such as angiogenesis, immune suppression, and tumor metastasis; hence, TAMs have emerged as a hot topic of research in cancer therapy. This review focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 76 publications
1
121
0
Order By: Relevance
“…Due to the influence of cytokines in the TME, TAMs can be divided into two distinct polarized forms, M1 and M2 macrophages. The former is responsible for killing tumor cells; the latter is able to promote tumor growth (223). Macrophage M1/M2 polarization is adjustable and reversible.…”
Section: Regulation Of Macrophages By Adam17mentioning
confidence: 99%
“…Due to the influence of cytokines in the TME, TAMs can be divided into two distinct polarized forms, M1 and M2 macrophages. The former is responsible for killing tumor cells; the latter is able to promote tumor growth (223). Macrophage M1/M2 polarization is adjustable and reversible.…”
Section: Regulation Of Macrophages By Adam17mentioning
confidence: 99%
“…ROCK regulating the phosphorylation of STAT3 to promote macrophage polarisation is not a new concept, and has previously been reported in chronic graft versus host disease, hepatocellular carcinoma and breast cancer. 88 , 89 , 90 To investigate the mechanism by which ROCK regulates macrophage polarisation, we elevated the phosphorylation of STAT3 in bleomycin‐ and radiation‐induced PF cells treated with WXWH0265, a ROCK inhibitor. The phosphorylation of STAT3 was inhibited by the decrease in M2 macrophage polarisation after WXWH0265 treatment, which verified our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) in the tumor microenvironment are heterogeneous subsets, including M1 antitumor and M2 tumor-promoting phenotypes. TAMs primarily exert M2-like tumor-promoting effects in the TME and regulate various malignant effects, such as angiogenesis, immunosuppression, and tumor metastasis (33,34). Prior work has reported that each of M1 and M2 macrophages are produced by M0 is a quiescent state of macrophages with no particular role until they become polarized (35).…”
Section: Discussionmentioning
confidence: 99%